Air Measurement in Residential Hydrometer: Preliminary Results - Sirtoli, Vinicus Grando; Watabe Sato, Airton Akio; Bertemes Filho, Pedro (Ingeniería Solidaria, 2016)
Introduction: This article was created by the 2015research for the Electronics’ Engineering Degree of the University of Santa Catarina’s department (Brazil). Most systems that measure water and are used in residences can register the air flow that may be present in the distribution system. This problem is hard to measure, since it’s a combination of liquid and gas. The purpose of this article is to identify and quantify the sensibility of residential hydrometers to the air volume registered.Methodology: To accomplish it, an experimental hydraulic circuit was developed, and sensors were deployed to monitor the water entry and exit of the system, composed by two warehouses. One warehouse stored water for the circulation of the hydraulic drainage, while the other stored the total amount of water in the system. The water level in the storehouses is controlled with ultrasonic and potentiometer sensors. A spinner is used to estimate the total water volume that enters the system by measuring its volumetric flow.Results: The results show that the hydrometer is very sensible to the air flow and that it can measure up to 44% of air in the air/water combination. The difference in the estimated water volume in the spinner and in the hydrometer was of 3,7 liters.Conclusions: The hydrometer is especially sensible to air presence in the residential hydraulic pipelines under normal conditions of a nominal flow of approximately 1,5 m3 /h.
Keywords: hydraulic circuit; hydrometer; electronic instrumentation; air/water combination; spinner